Effect of Ti-doping on peeling resistance of primary M7C3 carbides in hypereutectic FeCrC hardfacing coating and γ-Fe/M7C3 interfacial bonding strength. (1st December 2021) - Shao, Wei; Zhou, Yefei; Zhou, Lei; Rao, Lixiang; Xing, Xiaolei; Shi, Zhijun; Yang, Qingxiang
Graphical abstract: Highlights: The hardness and wear resistance of the FeCrC hardfacing coating are improved after adding Ti element. The orientation relationship of eutectic austenite/primary M7 C3 carbide is γ-Fe(1 1 1)//(Cr, Fe)7 C3 (1 0 1 ¯ 0). Ti-doping can effectively inhibit the initiation and propagation of cracks. The interfacial adhesion strength of γ-Fe//M7 C3 is enhanced after adding Ti element. Abstract: Alloying element Ti plays an important role in improving the mechanical properties of hypereutectic FeCrC hardfacing coating, but its peeling resistance have been neglected. Here, the hardness and wear rate of the hypereutectic FeCrC and FeCrCTi hardfacing coatings were measured. The crystal structure and orientation relationship of primary M7 C3 carbide and eutectic austenite matrix were confirmed. Then, the interface properties of γ-Fe//M7 C3 (Ti) interface were calculated by first principles. The results show that the micro-Vickers and macroscopic Rockwell hardness of the FeCrCTi hardfacing coating are increased, and its wear rate is decreased from (4.33 ± 0.333) × 10 −6  mm 3 /Nm to (3.64 ± 0.366) × 10 −6  mm 3 /Nm. The Ti-doping can effectively inhibit the initiation and propagation of cracks and improve the peeling resistance of M7 C3 carbide. Meanwhile, the orientation relationship of eutectic austenite/primary M7 C3 carbide is γ-Fe(1 1 1)//(Cr, Fe)7 C3 (10 1 ¯ 0). Among CFe1, CrFe1 and FeFe1 interfaces, interface energy of FeFe1 model is the smallest (1.954 J/m 2 ), and its adhesion work ( W ad ) is the largest (0.756 J/m 2 ). Moreover, W ad of Ti-doped interface (4.123 J/m 2 ) is larger than that of FeFe1 one (3.045 J/m 2 ) after relaxed, which indicates Ti-doping is beneficial to enhance adhesive strength between γ-Fe//M7 C3 interfaces, which improves the peeling resistance of M7 C3 carbide.